The non-interventional approach to papillary thyroid microcarcinomas. An "active surveillance" dilemma. (June 2019) - Paparodis, Rodis D.; Bantouna, Dimitra; Imam, Shahnawaz; Jaume, Juan Carlos
Abstract: Background: Recent studies suggest that papillary-thyroid-microcarcinomas (PTMi) and follicular-variant-papillary-thyroid-cancers (FVPTC) are less aggressive overall. Our observations argue against. Objectives: To assess whether PTMi and FVPTC are indeed low-risk and could be safely followed without intervention. Methods: We prospectively collected data of subjects with PTC on pathology post-thyroidectomy. Odds ratios (OR) were calculated with Fisher's exact test and differences between means were calculated using Mann Whitney's test. Results: 696 met inclusion-criteria; 436 had macrocarcinomas (PTMa) and 260 had PTMi. PTMa were statistically significantly more likely to present multifocal [44.0% vs.28.1%], with extrathyroidal extension [22.1% vs.3.4%], lymph nodes involvement [25.5% vs.8.8%] and local invasion [3.1% vs.0.4%] (p < 0.05 for all), but not with distant metastasis [3.4% vs.1.3%, p > 0.05]. Therefore, PTMi measuring down to 0.01 cm, harbored aggressive features. We also identified 174 cases with FVPTC and 522 subjects with non-FVPTC. FVPTC had lower incidence of multifocality [40.1%, vs.60.9%], extrathyroidal extension [8.6% vs.17.4%] and lymphatic involvement [5.2% vs.24.0%], but not distant metastasis or local invasion [p > 0.05 for all]. Therefore, FVPTC measuring down to 0.5 cm, also harbored aggressive features. Conclusions: PTMi and FVPTC aggressive features are substantial enough to require careful evaluation, independent of their original tumor size before defaulting to just "active surveillance." Highlights: We stratified a risk comparison between micro and macro Papillary thyroid carcinomas. We include the controversially less aggressive Follicular Variant of Papillary Thyroid Carcinoma. Our paper provides complementary tools to current guidelines to assess thyroid cancer risk.